DR. ABDÜLHAK ADNAN ADIVAR (1882-1955) - Ada, Turhan (NOBEL ILAC, 2024)
Doctor Adnan (Ad & imath;var), who was next to Mustafa Kemal Pasha with his wife Halide Edip Han & imath;m during the National Struggle, was present at the opening of the Grand National Assembly on April 23, 1920 and was elected the first minister of health. During this duty, which lasted for about a year, Doctor Adnan Bey, who carried out important actions with extremely limited opportunities, was not only strongly criticized on the floor of the parliament, but also did not find the support he expected. However, despite all these difficulties, he provided the elimination of important deficiencies in the field of health, both in terms of institutional and legal infrastructure, was directly interested in the health problems of the people of the region, and was in close contact with Mustafa Kemal Pasha and his mother.
Keywords: Adnan Ad & imath; var; national struggle; the first Turkish grand national assembly; ministers health; General & Internal Medicine